Narcissistic leadership : Narcissus on the couch - Kets de Vries, Manfred F. R. (Routledge, 2025)
"Narcissism has become a contemporary pandemic that seems to have been normalized, accepted and even celebrated, both in society at large and by some of our political and business leaders. In this book, world-renowned psychology and leadership thinker, Manfred Kets de Vries, explains this modern phenomenon, and imagines how you would help the narcissist on the notional 'coach's couch'. Consumerism, competitive urges, individualism, and identity politics are examples of how our present-day culture has reinforced the self-glorification that drives narcissism-this cult of the self. Although a healthy competitive spirit is part of human nature, for narcissistic people it can turn into an all-consuming character trait. They view the world almost exclusively in terms of "winners" and "losers", and to lose is unacceptable. And social media seems to provide ample opportunities to magnify the competitive or narcissistic disposition present in all of us. Starting with an in-depth discussion of the ancient myth of Narcissus, the various shapes in which narcissism expresses itself are highlighted. Subsequently, taking an individual and group perspective, various strategies for how to manage narcissistic people are explored. Using case examples of interpersonal and group approaches to change, concepts such as the working alliance, the emotional seesaw, the grey rock approach, boundary management, Socratic questioning, the sandwich tactic, and the need to be empathic, are introduced. Also, referring to change in a group setting, the importance of the psychological dynamics of the group-as-a-whole is presented. Narcisstic Leadership offers a unique and original approach to exploring the ramifications of narcissistic leadership and will be of interest to the general reader as well as the key audiences of organizational leaders, psychoanalysts, coaches, psychotherapists, sociologists and social psychologists"--